Eksistensi dan Kegunaan Talempong Pacik dalam Upacara Adat Nagari - Fazrul Muhammad; Syahri Anton (INDO PUBLISHING, 2026)
The Talempong Pacik is a traditional Minangkabau musical instrument played by holding (pacik) with the hands and striking with a special mallet. In Nagari Kinari, Solok Regency, the Talempong Pacik is not merely a form of entertainment but an integral part of traditional ceremonies. This study aims to examine the existence and use of the Talempong Pacik within the context of traditional ceremonies in Nagari Kinari. Using qualitative methods with an ethnomusicological approach, data were collected through observation, interviews with traditional leaders (Niniak Mamak) and musicians, and documentation studies. The results indicate that the Talempong Pacik remains well-preserved in Nagari Kinari due to its sacred function as a medium for socio-cultural communication, an accompaniment to traditional processions (Baralek, Batagak Penghulu), and a symbol of communal prestige. The instrument's sustainability is supported by a strong system of value inheritance within the Nagari Kinari traditional structure.